Motivação para o ensino e aprendizagem dos números complexos: uma abordagem com aplicações - Moreira, Agnaldo Antonio (2018)
Literature shows that motivating teachers and students for studying complex numbers in high school can be a challenging task. This work investigates such issue and proposes an approach for teaching complex numbers based on their history, applications and fractals. In addition it provides some digital resources to explore interactive lessons and activities of this content.